High-resolution image processing and entity recognition algorithm based on artificial intelligence - Sun Yutong (Journal of Intelligent Systems)
With the popularity of high-resolution devices such as high-definition, ultra-high-definition televisions, and smartphones, the demand for high-resolution images is also increasing, which puts forward higher requirements for high-resolution image processing and entity recognition technology.